Discovery of the novel HLA‐DRB1*04:05:14 allele in a Taiwanese unrelated haematopoietic stem cell donor by a sequence‐based typing method. (7th November 2012) - Yang, K. L.; Lee, S. K.; Kao, R. H.; Lin, C. L.; Lin, P. Y.
Summary We report here a de novo HLA‐DRB1*04 allele, DRB1*04:05:14, discovered in a Taiwanese unrelated volunteer bone marrow stem cell donor by a sequence‐based typing method. In exon 2, the DNA sequence of DRB1*04:05:14 is identical to the sequence of DRB1*04:05:01 except the nucleotide at positions 321 where C is replaced by T (at codon 78; TAC→TAT). Due to the silent mutation, the nucleotide substitution produced no amino acid variation in comparison with DRB1*04:05:01. We assume DRB1*04:05:14 was derived from DRB1*04:05:01 via a point mutation. The probable HLA‐A, ‐B and ‐DRB1 haplotype in association with DRB1*04:05:14 may be deduced as A*11‐B*55‐DRB1*04:05:14. We here report the Taiwanese ethnicity of DRB1*04:05:14.